Multiple Supra-aortic Stenting for Takayasu Arteritis: Extensive Revascularization and Two-Year Follow-up - Takahashi, Jun C. (AJNR Am J Neuroradiol, 2002)
Summary: A patient with Takayasu arteritis with multiple supra-aortic lesions underwent successful treatment with two-staged stent implantation. Stenotic bilateral common carotid, innominate, and left subclavian arteries were dilated, and no restenosis was observed during the follow-up period of 2 years despite recurrent inflammation. Stenting for supra-aortic vessels in cases of Takayasu arteritis has rarely been reported, and to our knowledge, this is the first report of multiple stent placement for all the supra-aortic branches involved.